Coping with the treatment of sickle cell disease: challenges and perspectives experienced by the family - Cruz, Rhalliete Souza (2020)
Sickle cell disease is a serious hemolytic disorder caused by genetic mutation, which causes production of the mutant hemoglobin S. The objective of this paper was to understand how family members cope with the treatment of sickle cell disease. This is a field research with a qualitative approach. The study used as a basis interviews conducted with mothers of children and adolescents with sickle cell disease assisted by the Reference Center of a city in the state of Bahia, Brazil, in the year 2017. Based on the information collected it was possible to perceive that people with sickle cell anemia during good require specific treatments that may be performed by themselves or with the help and encouragement of others, usually family members. It is very important to reflect on the effectiveness of treatment not only from the technical point of view but also from the point of view of the patient, his family and society